Knowledge, Attitudes and Practices towards Infection Prevention Control among Healthcare Workers in Selected Hospitals Located in Karongi district, Rwanda - Jean Claude Haguminshuti; Ernest Safari; Monica Mochama; Erigene Rutayisire (Journal of Public Health International, 2022)
Most hospitals have infection prevention and control committees but some of them are struggling to maintain and to apply infection prevention and control protocols due to lack of enough resources. Healthcare workers’ (HCWs) knowledge, attitude and practices (KAP) of infection prevention and control procedures are crucial for effective infection prevention and control (IPC). The study aimed to assess HCW’s KAP towards IPC in Rwanda. A cross-sectional hospital based study was directed in three hospitals in Karongi district from February to March 2022. Data were collected from 215 healthcare workers using a pre-tested self-administered questionnaire using a stratified sampling technique. Data were collected, checked, coded, and entered into the Kobo Collect Toolbox before being transferred to SPSS version 21 for analysis. Bivariate and multiple logistic regression analyses were performed. The KAP Score was also calculated. P-values of less than 0.05 were considered statistically significant. We found that 50.7% of HCWs were males, 63.3% were between the ages of 18 and 58.2% had a secondary education. The overall 78.6% of HCWs demonstrated high level of knowledge, 79.5% with a positive attitude, and 63.3% with good IPC practice. The results revealed that being over 45 years old(AOR=3.1;95%,CI=(2.16-5.25; p=0.024) having university level(AOR=3.3); 95%CI=(1.56-7.56;p=0.035), working experience between 5-10years(AOR=1.7; 95%CI=(1.37-5.45); (p=0.003), having high level of knowledge (AOR=2.7;95%CI: (1.68–7.95; p=0.045)and positive attitude(AOR=2.3; 95%CI:(1.36-7.72); p=0.017) towards IPC were associated with IPC good practice. Improving institutional supplies such as hand hygiene supplies, PPE, water supply and other facilities can improve safe infection prevention and control.
Keywords: Knowledge